Pendekatan Komunikasi Organisasi Dalam Pengelolaan Sampah di UPTD Tempat Pembuangan Akhir Ciangir Kota Tasikmalaya - Hartanto, Beni; Sudrajat, Deni; Heri Widodo, Teguh; Badrujaman, Sopi; Badriatin, Tine (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
The research was conducted with the aim of analyzing the organizational communication approach in waste management at the final disposal site of UPTD Ciangir, Tasikmalaya City. The theory used in this study is based on the opinion of experts relevant to the research problem, where the communication approach is measured in terms of internal communication and external communication. This research method uses qualitative methods with the aim of uncovering the communication barriers related to waste management at the UPTD final disposal site in Ciangir, Tasikmalaya City. The research informants were government officials, and employees of UPTD TPA Ciangir and Tasikmalaya City Environmental Department. Data analysis techniques are performed through data reduction, data display, verification, and drawing conclusions. Based on the results of this study, it appears that the communication carried out by UPTD TPA Ciangir Tasikmalaya City with an internal communication approach is going well, while for the external communication it is still not effective, therefore it requires yet another communication strategy that can solve waste management problems at TPA Ciangir Tasikmalaya City.